Studi Kasus Pengobatan Eczema Kronis Menggunakan Formula Herbal Si Wu Xiao Feng San - Handojo Handojo; Ferdinand Ferdinand (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Skin Allergy is a symptom of an allergic reaction in the body that appears on the skin. Eczema is one of the most common forms of allergies. This symptom is generally described as a chronic inflammatory skin disease which is enough to interfere with the patient's activities and confidence. The Chinese Medicine approach which is based on the theory of TCM (Traditional Chinese Medicine) emphasis on diagnosis, syndrome differentiation and herbal therapy for Eczema has been widely applied and is able to give good results. This study aims to assess the effectiveness of Si Wu Xiao Feng Shan's herbal formula in improving symptoms of chronic eczema, with blood deficiency syndrome accompanied by dry wind. The Pretest-Posttest One Group Design research method observed the results of four TCM examinations, coupled with SCORAD atopic dermatitis index measurements, showing improvement in patient S after using the herbal formula Si Wu Xiao Feng Shan for 2x a week for 1 month. Keywords: Chronic Eczema Treatment, Herbal Formulas, Si Wu Xiao Feng San Abstrak Alergi Kulit adalah gejala reaksi allergen pada tubuh yang nampak pada kulit. Eczema adalah salah satu bentuk alergi yang cukup banyak ditemui. Gejala ini umumnya dikategorikan sebagai penyakit inflamasi kulit kronis yang cukup mengganggu aktivitas dan kepercayaan diri pasien. Pendekatan Pengobatan Tionghoa yang berdasarkan teori TCM (Traditional Chinese Medicine) menekankan pada diagnosa, diferensiasi sindrom dan terapi herbal untuk Eczema telah banyak diterapkan dan mampu memberikan hasil yang baik. Penelitian ini bertujuan untuk menilai efektivitas formula herbal Si Wu Xiao Feng Shan dalam memperbaiki gejala Eczema kronis, dengan sindrom defisiensi darah disertai angin kering. Metode penelitian Pretest-Posttest One Group Design mengamati hasil empat pemeriksaan secara TCM, ditambah dengan index pengukuran atopic dermatitis SCORAD, menunjukkan perbaikan pada pasien S setelah menggunakan formula herbal Si Wu Xiao Feng Shan selama 2x dalam seminggu selama 1 bulan Kata kunci: Pengobatan Eczema Kronis, Formula Herbal, Si Wu Xiao Feng San